2017
DOI: 10.1016/j.jiph.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A survey of awareness related to the use of antibiotics for dental issues among non-medical female university students in Riyadh, Saudi Arabia

Abstract: Inappropriate use of antibiotics may lead to adverse side effects. This cross-sectional survey aimed to investigate the knowledge and attitude of female non-medical students regarding the medical and dental use of antibiotics. Four hundred validated self-administered questionnaires were distributed in Princess Norah Bint-Abdurrahman University, Riyadh, Saudi Arabia. The questionnaire included questions about accessibility, attitude toward usage, efficacy, side effects, resistance, and usage for dental issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…These studies indicated that there was frequent prescription of antibiotics in situations where they are not necessary or indicated [ 12 , 13 ]. Moreover, a survey that was distributed amongst Riyadh’s non-medical female university students investigating their knowledge and attitudes regarding the medical and dental use of antibiotics revealed that there are misconceptions and a negative attitude towards antibiotics usage in treating dentistry-related problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that there was frequent prescription of antibiotics in situations where they are not necessary or indicated [ 12 , 13 ]. Moreover, a survey that was distributed amongst Riyadh’s non-medical female university students investigating their knowledge and attitudes regarding the medical and dental use of antibiotics revealed that there are misconceptions and a negative attitude towards antibiotics usage in treating dentistry-related problems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, 80% of the population were found to be self-medicating for dental pain of which antibiotics were the main medications used [ 9 ]. In contrast, a survey investigated a sample of Saudi papulation revealed a more positive attitude in regard to antibiotics of which 77.8% of the sample used them according to the doctor’s prescription only [ 17 ]. Several substances were used without professional consultation.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings of the previous studies cannot be generalized as the samples were either dental patients or university students, which do not accurately represent the Saudi population. In addition, most of the reported studies were limited to investigate the practice of self-medication using antibiotics only [ 9 , 17 ]. The current study aims to assess the patterns of self-medication for the management of oral health problems among adults living in Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…However, some self-reported data and questionnairebased studies have evaluated awareness, knowledge, habits, and attitudes in relation to prescribing dental antibiotics among Saudi dentists or dental students. [10][11][12][13][14] The current study, first of its kind, evaluated and analyzed a total of 43,255 dental visits over a two-year period. It identified factors such as the prescription of antibiotics in dental consultations, including patients' age and gender, dentists' gender, dentists' specialty, and dentists' diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated awareness, knowledge, habits, and attitudes in relation to prescribing dental antibiotics among Saudi dental practitioners or dental students. [10][11][12][13][14] These studies concluded that poor practice of prescribing dental antibiotics was prevalent among Saudi dentists and dental students. 11,14 The studies also highlighted that Saudi dentists lacked knowledge and misused antibiotic prescription in endodontic therapy, 12 emphasizing the improvement of knowledge among Saudi dentists regarding odontogenic infection management.…”
Section: Introductionmentioning
confidence: 99%